Preparation method for preparing ordered membrane electrode by using two-step electrodeposition method and membrane electrode
Through two-step electrodeposition method, a hydrophilic layer and a perfluorosulfonic acid resin film are formed on the surface of the gas diffusion layer, which solves the problem of controlling the morphology and crystal surface structure of the precious metal catalyst, improves the reaction rate and battery performance of the membrane electrode, and is suitable for industrialization Production.
Patent Information
- Application Number
- CN202411393722.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, when preparing precious metal catalysts, the use of additives or templates will affect the catalytic performance, and direct electrochemical deposition can easily lead to local hydrolysis of platinum salts and coarse platinum grains, making it difficult to control the morphology and crystal surface structure of the nanoparticles.
Using a two-step electrodeposition method, first form a hydrophilic layer on the surface of the microporous layer of the gas diffusion layer, anchor and uniformly distribute Pt nanoparticles, and then wrap the perfluorosulfonic acid resin film to construct an orderly three-phase interface to improve the Catalytic properties.
It improves the effective contact area and stability of Pt, reduces the mass transfer resistance of the membrane electrode, enhances the reaction rate and battery performance, and is suitable for industrial production.
Smart Images

Figure CN119297301A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a method for preparing an ordered membrane electrode by a two-step electrodeposition method and a membrane electrode. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is the most effective device for converting the chemical energy of hydrogen fuel into electrical energy. In the process of PEMFC industrialization, its cost problem has always been one of the core issues that plague its development. At present, reducing the amount of precious metal catalysts in membrane electrode (MEA) is the main way to reduce MEA cost.
[0003] In order to improve the catalytic performance of precious metal Pt and reduce the amount of Pt used, a large number of studies have focused on the preparation of Pt micro / nanoparticle catalysts with controllable micromorphology and crystal surface structure. Commonly used preparation methods include seed growth method, microemulsion method, hydrothermal synthesis method, template method, etc. However, most of the above preparation methods require the introduction of specific additives or templates, and thus still have the following problems: (1) These organic or inorganic additives will be adsorbed on the surface of the catalyst particles, which will have an adverse effect on their catalytic performance; (2) The subsequent removal of the adsorbents on the surface of the catalyst particles or the removal of the template may also destroy the morphology or structure of the surface of the prepared micro / nanoparticles.
[0004] Direct electrochemical deposition can selectively deposit metal catalysts on a carrier that has both electron channels and ion transport channels and is in contact with the proton membrane, showing a higher catalyst utilization rate than the traditional method of bonding Pt / C catalysts with proton exchange membrane electrolyte solutions. However, when the precious metal platinum is directly deposited on the porous carbon electrode bonded to the proton exchange membrane, there are problems such as local hydrolysis of platinum salts due to hydrogen evolution, collapse of the porous carbon layer, and coarseness of the deposited platinum grains.
[0005] Therefore, developing a simple membrane electrode preparation method that can easily control the surface morphology and crystal structure of precious metal nanoparticle catalysts is an urgent problem to be solved in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing an ordered membrane electrode using a two-step electrodeposition method and a membrane electrode. The present invention prepares an ordered membrane electrode by a two-step electrodeposition method: first, a hydrophilic layer containing an aminosilane coupling agent is formed on the surface of a microporous layer, and then a first electrodeposition is performed to deposit Pt nanoparticles on the surface of the hydrophilic layer to construct an ordered Pt nanoarray, wherein the aminosilane coupling agent has an anchoring and uniform distribution effect on the subsequently electrodeposited Pt nanoparticles, thereby increasing the effective contact area and stability of Pt; and then a second electrodeposition is performed to wrap a layer of perfluorosulfonic acid resin film on the surface of the Pt particles to effectively construct a three-phase interface, so that the effective reaction area is extended to the entire cathode catalyst layer, thereby improving the membrane electrode reaction rate and the performance of the battery, and the preparation method is simple and suitable for large-scale industrial production and promotion and application.
[0007] To achieve the above object, the present invention first provides a method for preparing an ordered membrane electrode by a two-step electrodeposition method, comprising the following steps:
[0008] S1, providing a gas diffusion layer, and forming a hydrophilic layer on the surface of the microporous layer of the gas diffusion layer;
[0009] S2, first electrodeposition: immersing the product of step S1 in a platinum-containing electrodeposition solution to deposit metal Pt particles on the surface of the hydrophilic layer, and drying after the reaction is completed for later use;
[0010] S3, second electrodeposition: immersing the product of step S2 in a perfluorosulfonic acid resin solution, depositing a perfluorosulfonic acid resin film on the surface of the metal Pt particles to form a cathode catalyst layer;
[0011] S4, laminating the product of step S3 with a proton exchange membrane and an anode diffusion layer in sequence, and compounding them by hot pressing to obtain the ordered membrane electrode.
[0012] Preferably, the platinum-containing electrodeposition solution comprises: chloroplatinic acid and perchloric acid.
[0013] Preferably, in the platinum-containing electrodeposition solution, the mass fraction of the chloroplatinic acid is 0.5%-3%, and the mass fraction of the perchloric acid is 0.1%-4%.
[0014] Preferably, the mass fraction of the perfluorosulfonic acid resin solution is 0.1%-20%.
[0015] Preferably, in step S2, a constant voltage is used for the first electrodeposition reaction, the voltage is controlled at -0.1V to -1V, and the electrodeposition time is 10min to 60min;
[0016] In the step S3, a constant voltage is used to carry out the second electrodeposition reaction, the voltage is controlled at -0.1V to -0.4V, and the electrodeposition time is 2min to 20min.
[0017] Preferably, in step S1, the gas diffusion layer is immersed in a hydrophilic solution, and the hydrophilic layer is formed on the surface of the microporous layer of the gas diffusion layer through centrifugation and ultrasonic action.
[0018] Preferably, the hydrophilic solution comprises: an aminosilane coupling agent, a perfluorosulfonic acid resin, an organic solvent and water, wherein the concentration of the aminosilane coupling agent is 90wt%-99wt%, and the concentration of the perfluorosulfonic acid resin is 0.01wt%-2wt%.
[0019] Preferably, in step S1, the gas diffusion layer is composed of a support layer and a microporous layer, the support layer has a thickness of 120 μm to 170 μm, and a total pore area of 50 m 2 / g-80m 2 / g, average pore size 60nm-80nm, porosity 25%-35%; the thickness of the microporous layer is 30μm-50μm, the total pore area is 50m 2 / g-100m 2 / g, average pore size 0.5nm-2nm, porosity 30%-50%.
[0020] Another aspect of the present invention provides an ordered membrane electrode prepared by the above-mentioned preparation method.
[0021] Another aspect of the present invention provides a fuel cell, which comprises the above-mentioned ordered membrane electrode.
[0022] Compared with the prior art, the beneficial effects of the present invention include at least:
[0023] 1. The present invention provides a method for preparing an ordered membrane electrode by a two-step electrodeposition method. Specifically, a hydrophilic layer is first prepared on the surface of a microporous layer of a gas diffusion layer, wherein the hydrophilic layer comprises an aminosilane coupling agent, and the aminosilane coupling agent has the function of anchoring and uniformly distributing the subsequently electrodeposited Pt nanoparticles, thereby increasing the effective contact area and stability of Pt, reducing the mass transfer resistance of the membrane electrode, facilitating the transmission of gas, and improving the membrane electrode reaction rate; then a first electrodeposition is performed: metal Pt nanoparticles are deposited on the surface of the hydrophilic layer to construct an ordered Pt nanoarray; and then a second electrodeposition is performed: a uniform and ultra-thin perfluorosulfonic acid resin film is wrapped on the surface of the Pt nanoparticles to effectively construct a three-phase interface and maximize the number of three-phase interfaces, so that the effective reaction area is extended to the entire cathode catalyst layer, thereby improving the membrane electrode reaction rate and the performance of the battery.
[0024] 2. The hydrophilic layer of the present invention also contains perfluorosulfonic acid resin, which is used to improve the conductivity of the hydrophilic layer, facilitate the subsequent electrodeposition reaction, and improve the efficiency of the electrodeposition reaction.
[0025] 3. The gas diffusion layer of the present invention is composed of a support layer and a microporous layer. The average pore size of the support layer is 60nm-80nm, and the porosity is 25%-35%; the average pore size of the microporous layer is 0.5nm-2nm, and the porosity is 30%-50%. The rich pore structure in the diffusion layer of the present invention provides more channels for the transportation of oxygen, which greatly guarantees the construction of the three-phase interface; the smaller porosity and pore size in the micropores enhance the moisture retention capacity of the membrane electrode, which helps to improve the performance of the membrane electrode under low humidification conditions.
[0026] 4. The preparation method provided by the present invention has simple process, easily controllable conditions and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A flow chart of the method for preparing an ordered membrane electrode using a two-step electrodeposition method provided by the present invention.
[0028] Figure 2 This is a schematic diagram of the structure of a gas diffusion layer with a hydrophilic layer prepared according to an embodiment of the present invention.
[0029] Figure 3 This is a schematic diagram of the structure of an ordered membrane electrode produced according to an embodiment of the present invention.
[0030] Figure 4 FIG. 4 is a schematic diagram of the operation of an electrodeposition reaction in one embodiment of the present invention.
[0031] Figure 5 Schematic diagram of the morphology of Pt particles deposited under different deposition voltages in the first electrodeposition step in Examples 1-3 of the present invention; wherein, Figure a: the deposition voltage is -0.2V, Figure b: the deposition voltage is -0.6V, and Figure c: the deposition voltage is -0.8V.
[0032] Figure 6 Comparison of polarization characteristic curves of the membrane electrode prepared in Example 4 of the present invention.
[0033] Figure 7 The figure is a comparison of polarization characteristic curves of the membrane electrode prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0035] As mentioned above, developing a simple membrane electrode preparation method that can easily control the surface morphology and crystal structure of precious metal nanoparticle catalysts is an urgent problem to be solved in this field.
[0036] To this end, the present applicant has conducted extensive research and finally provided a method for preparing an ordered membrane electrode using a two-step electrodeposition method, such as Figures 1 to 3 As shown, the following steps are included:
[0037] S1, providing a gas diffusion layer, and forming a hydrophilic layer on the surface of the microporous layer of the gas diffusion layer.
[0038] In this embodiment, a hydrophilic solution is first prepared, and the hydrophilic solution includes: aminosilane coupling agent, perfluorosulfonic acid resin, organic solvent (alcohol, such as isopropyl alcohol) and water; the gas diffusion layer is immersed in the prepared hydrophilic solution, rotated and centrifuged for 5min-90min, and then ultrasonically treated for 10min-30min to form a hydrophilic layer on the surface of the microporous layer of the gas diffusion layer.
[0039] It is particularly pointed out that in the hydrophilic solution, the role of the aminosilane coupling agent is to form a hydrophilic layer on the surface of the microporous layer, which is hydrophilic and is conducive to the anchoring and uniform distribution of the metal Pt during the subsequent first electrodeposition, thereby increasing the effective contact area and stability of Pt, reducing the mass transfer resistance, facilitating the transmission of gas, and increasing the membrane electrode reaction rate. More importantly, the combined effect of the silane coupling agent and the deposition voltage makes the deposition of Pt nanoparticles anisotropic, which helps to form a nanoarray with a large specific surface area; otherwise, if the surface of the gas diffusion layer does not have the hydrophilic layer containing the aminosilane coupling agent, the Pt particles formed by the electrodeposition will be dispersed in the solution, and the metal Pt particles cannot be deposited on the surface of the gas diffusion layer without the hydrophilic layer, resulting in the failure of the preparation of the cathode catalyst layer. Among them, according to the number of amino groups, the aminosilane coupling agent can be divided into monoamino, diamino, triamino and polyamino groups, such as 1,3-aminopropyltrimethoxysilane (APS).
[0040] The role of perfluorosulfonic acid resin (Nafion) is to improve the conductivity of the hydrophilic layer, because the aminosilane coupling agent itself does not have conductive properties, but it can be conductive after being compounded with Nafion, thereby facilitating the subsequent electrodeposition reaction and improving the efficiency of the electrodeposition reaction.
[0041] It should also be noted that it is difficult to allow the silane coupling agent and the perfluorosulfonic acid resin to enter the microporous layer by conventional immersion. Therefore, this embodiment uses a method of rotary centrifugation and ultrasonic treatment to allow the silane coupling agent and the perfluorosulfonic acid resin to smoothly infiltrate the microporous layer and ultimately form the hydrophilic layer on the surface of the microporous layer of the gas diffusion layer.
[0042] In some embodiments, the concentration of the aminosilane coupling agent in the hydrophilic solution is 90 wt %-99 wt %, and the concentration of the perfluorosulfonic acid resin is 0.01 wt %-2 wt %.
[0043] The gas diffusion layer is composed of a support layer and a microporous layer. The thickness of the support layer is 120 μm to 170 μm, and the total pore area is 50 m 2 / g-80m2 / g, average pore size 60nm-80nm, porosity 25%-35%; the thickness of the microporous layer is 30μm-50μm, the total pore area is 50m 2 / g-100m 2 / g, average pore size 0.5nm-2nm, porosity 30%-50%. The structure and preparation method of the gas diffusion layer can refer to the general method in the field, and will not be specifically described or limited here. It should be pointed out that the rich pore structure in the diffusion layer of the present invention provides more channels for the transport of oxygen, which greatly guarantees the construction of the three-phase interface; the smaller porosity and pore size in the micropores enhance the moisture retention ability of the membrane electrode and help improve the performance of the membrane electrode under low humidification conditions. It is particularly pointed out that when preparing the hydrophilic layer, the perfluorosulfonic acid resin and silane coupling agent in the hydrophilic solution enter the microporous layer, which makes the microporous layer have a smaller porosity, further enhancing the membrane electrode's control over water management and improving the performance of the membrane electrode.
[0044] The product structure of step S1 is as follows Figure 2 shown.
[0045] S2, first electrodeposition: immersing the product of step S1 in a platinum-containing electrodeposition solution to deposit metal Pt particles on the surface of the hydrophilic layer, and drying after the reaction is completed for later use.
[0046] In this step, firstly, a platinum-containing electrodeposition solution is prepared, wherein the platinum-containing electrodeposition solution comprises: chloroplatinic acid and perchloric acid; the gas diffusion layer having a hydrophilic layer obtained in step S1 is immersed in the platinum-containing electrodeposition solution, and a constant voltage is applied through an electrochemical workstation, the voltage is controlled at -0.1V to -1V, and the electrodeposition time is 10min-60min, thereby depositing metal Pt particles on the surface of the hydrophilic layer; after the reaction is completed, the above-mentioned product is taken out and placed in a 60°C vacuum drying oven for drying for 6h for standby use.
[0047] In some embodiments, the mass fraction of chloroplatinic acid is 0.5%-3%, and the mass fraction of perchloric acid is 0.1%-4%.
[0048] In some embodiments, the mass fraction of the first electrodeposited Pt noble metal is 2%-10%, preferably 5%.
[0049] S3, second electrodeposition: immersing the product of step S2 in a perfluorosulfonic acid resin solution, depositing a perfluorosulfonic acid resin film on the surface of the metal Pt particles to form a cathode catalyst layer.
[0050] In this step, a perfluorosulfonic acid resin solution is first prepared, wherein the mass fraction of the perfluorosulfonic acid resin solution is 0.1%-20%, preferably 5%; the product obtained in step S2 is immersed in the perfluorosulfonic acid resin solution, and a constant voltage is applied through an electrochemical workstation, the voltage is controlled at -0.1V to -0.4V, and the electrodeposition time is 2min-20min, thereby depositing a uniform and ultra-thin perfluorosulfonic acid resin film on the surface of the metal Pt particles on the surface of the hydrophilic layer to form a cathode catalyst layer.
[0051] It should be pointed out that the prior art generally involves first spraying perfluorosulfonic acid resin onto the surface of the microporous layer, and then performing electrodeposition to reduce platinum. However, the number of three-phase interfaces (areas where reactions occur) is relatively small, and there is only an area where the perfluorosulfonic acid resin contacts the bottom of the platinum particles. In addition, the uneven distribution of the perfluorosulfonic acid resin results in a large oxygen mass transfer resistance. The present application first constructs an ordered Pt nanoarray through a first electrodeposition, and then uniformly deposits the perfluorosulfonic acid resin on the array surface through a second electrodeposition, so that the surface of the metal Pt particles is coated with a uniform and ultra-thin perfluorosulfonic acid resin film, which is beneficial to maximizing the number of three-phase interfaces, reducing the oxygen mass transfer resistance, and improving the performance of the membrane electrode under unit platinum loading.
[0052] S4, laminating the product of step S3 with a proton exchange membrane and an anode diffusion layer in sequence, and compounding them by hot pressing to obtain the ordered membrane electrode.
[0053] This step adopts the hot pressing method for bonding, that is, a certain pressure is applied at the glass transition temperature of the perfluorosulfonic acid resin to press the product of step S3 to which the perfluorosulfonic acid resin has been added, the perfluorosulfonic acid type proton exchange membrane and the anode diffusion layer to which the perfluorosulfonic acid resin has been added together to form an ordered membrane electrode assembly.
[0054] In some embodiments, the anode diffusion layer is prepared by spraying an anode catalyst layer slurry on the surface of a microporous layer of a gas diffusion layer to form an anode diffusion layer having an anode catalyst layer.
[0055] The product structure of step S4 is as follows Figure 3 shown.
[0056] Another aspect of the present invention provides an ordered membrane electrode prepared by the above-mentioned preparation method.
[0057] Another aspect of the present invention provides a fuel cell, which comprises the above-mentioned ordered membrane electrode.
[0058] The technical features of the present invention are described in detail below through examples and drawings. Unless otherwise specified, the instruments and materials described in the following examples can be obtained from commercial channels.
[0059] Example 1
[0060] A method for preparing an ordered membrane electrode by a two-step electrodeposition method comprises the following steps:
[0061] S1, providing a gas diffusion layer, and forming a hydrophilic layer on the surface of the microporous layer of the gas diffusion layer.
[0062] Preparation of gas diffusion layer: Vulcan XC-72 carbon powder was weighed, a small amount of deionized water was added and stirred to wet, and then a hydrophobic binder (PTFE in this embodiment), a mixed solution of ethanol and water were added, and ultrasonic dispersion was performed to obtain a uniform slurry; the above slurry was evenly coated on the surface of a commercial carbon paper (i.e., the support layer, with a thickness of 140 μm) by ultrasonic spraying, and then the carbon powder loading was determined by weighing method to be 4 mg / cm 2 , the content of PTFE is 25%; it is placed in a muffle furnace and heat treated at 340°C for 25 minutes. After cooling to room temperature, a microporous layer is formed on the surface of the support layer, and the thickness of the microporous layer is 40μm, thereby completing the preparation of the gas diffusion layer. In addition, in other embodiments, the hydrophobic binder can also be any one or more of PVDF, FEP, ECTE, ETFE, PFA, and PDMS.
[0063] Preparation of the hydrophilic layer: An aminosilane coupling agent, a perfluorosulfonic acid resin, isopropanol and water are mixed and stirred at room temperature for 4 hours to obtain a hydrophilic solution, wherein the concentration of the aminosilane coupling agent is 90wt%-99wt%, and the concentration of the perfluorosulfonic acid resin (Nafion) is 0.01wt%-2wt%; the gas diffusion layer prepared above is immersed in the hydrophilic solution, rotated and centrifuged for 5min-90min, and then subjected to ultrasonic treatment for 10min-30min (10min in this embodiment), thereby forming a hydrophilic layer on the surface of the microporous layer of the gas diffusion layer.
[0064] S2, first electrodeposition: immersing the product of step S1 in a platinum-containing electrodeposition solution to deposit metal Pt particles on the surface of the hydrophilic layer, and drying after the reaction is completed for later use.
[0065] Specifically, a platinum-containing electrodeposition solution is first prepared, wherein the platinum-containing electrodeposition solution comprises: chloroplatinic acid and perchloric acid, wherein the mass fraction of chloroplatinic acid is 0.5%-3%, and the mass fraction of perchloric acid is 0.1%-4%; the gas diffusion layer having a hydrophilic layer prepared in step S1 is immersed in the platinum-containing electrodeposition solution, and an electrochemical workstation (such as Figure 4 As shown in the figure, a constant voltage is applied, the voltage is controlled at -0.2V, and the electrodeposition time is 30min, thereby depositing metal Pt particles on the surface of the hydrophilic layer; after the reaction is completed, the above product is taken out and placed in a vacuum drying oven at 60°C for 6h for use.
[0066] S3, second electrodeposition: immersing the product of step S2 in a perfluorosulfonic acid resin solution, depositing a perfluorosulfonic acid resin film on the surface of the metal Pt particles to form a cathode catalyst layer.
[0067] Specifically, a perfluorosulfonic acid resin solution is first prepared with a mass fraction of 0.1%-20% (0.1% in this embodiment); the product obtained in step S2 is immersed in the perfluorosulfonic acid resin solution, and a constant voltage is applied through an electrochemical workstation, the voltage is controlled at -0.2V, and the electrodeposition time is 2min-20min, so that a uniform and ultra-thin perfluorosulfonic acid resin film is deposited and wrapped on the surface of the metal Pt particles on the surface of the hydrophilic layer to form a cathode catalyst layer.
[0068] In this embodiment, the Pt loading of the cathode catalyst layer is 0.15 mg Pt / cm 2 .
[0069] S4, sequentially laminating the product of step S3 with the proton exchange membrane and the anode diffusion layer, and compounding them by hot pressing to obtain the ordered membrane electrode. Specifically:
[0070] First, a proton exchange membrane (Nafion membrane) is provided and pretreated to remove organic and inorganic impurities on the proton exchange membrane: the proton exchange membrane is treated in a 5% hydrogen peroxide solution at 80°C to remove organic impurities; after being taken out, it is washed with deionized water and then treated in a dilute acid solution at 80°C to remove inorganic metal ions; then it is washed with deionized water and placed in deionized water for use.
[0071] Preparation of anode diffusion layer: water, isopropanol, Nafion, 40wt% Pt / C catalyst and PTFE were used to prepare a slurry. After ultrasonic stirring, it was sprayed on the surface of the microporous layer of a gas diffusion layer using an ultrasonic sprayer to form an anode catalyst layer. The platinum loading was 0.5mg Pt / cm 2 , and obtain the anode diffusion layer.
[0072] Then, the product of step S3 and the anode diffusion layer are placed on both sides of the proton exchange membrane respectively. During the bonding, the cathode catalyst layer and the anode catalyst layer are bonded to the two sides of the diaphragm respectively, and then placed between two stainless steel plates and sent to a hot pressing device: hot pressing for 180 seconds at a temperature of 130°C and a pressure of 2MPa, and then taken out and cooled to obtain the ordered membrane electrode. The active area of the membrane electrode is 50cm 2 .
[0073] Embodiment 2:
[0074] The difference from Example 1 is that in step S2, the constant deposition voltage used in the first electrodeposition reaction is -0.6V, and the other reaction conditions are the same as those in Example 1.
[0075] Embodiment 3:
[0076] The difference from Example 1 is that in step S2, the constant deposition voltage used in the first electrodeposition reaction is -0.8 V, and the other reaction conditions are the same as those in Example 1.
[0077] like Figure 5 As shown, the surface particle morphology of the cathode catalyst layer prepared in Examples 1-3 was observed by scanning electron microscopy. Figure 5 a is the morphology of Pt nanoparticles deposited in Example 1, Figure 5 b is the morphology of Pt nanoparticles deposited in Example 2, Figure 5 C is the morphology of Pt nanoparticles deposited in Example 3. It can be seen that the anisotropic properties of Pt nanoparticles are different under different electrodeposition voltages, so the morphology of the grown platinum arrays is different, and their performance is also different. Among them, compared with Examples 1 and 3, the platinum nanoarrays prepared in Example 2 have better morphology, larger specific surface area, and uniform distribution of nanoarrays, which helps to build more three-phase interfaces and improve membrane electrode performance.
[0078] Embodiment 4:
[0079] The difference from Example 1 is that in step S1, the concentration of the perfluorosulfonic acid resin in the hydrophilic solution is 0.1%; in the second electrodeposition reaction in step S3, the electrodeposition time used is 2 min, 5 min or 10 min, and the other reaction conditions are the same as in Example 1.
[0080] Embodiment 5:
[0081] The difference from Example 1 is that in step S1, the concentration of the perfluorosulfonic acid resin in the hydrophilic solution is 1%; in the second electrodeposition reaction in step S3, the electrodeposition time used is 2 min, 5 min or 10 min, and the other reaction conditions are the same as in Example 1.
[0082] Referring to GB / T 20042.5-2009, the polarization curve test of the proton exchange membrane fuel cell membrane electrode obtained in Examples 4 and 5 was carried out. The specific operating conditions are: the single cell operating temperature is 80°C, the anode is fed with pure hydrogen, the cathode is fed with atmospheric pressure oxygen, the cathode / anode feed is 1 / 1 times the stoichiometric ratio, and the discharge current density is 0.5A·cm -2 The results are shown in the attached Figure 6 and 7 .
[0083] Figure 6The polarization characteristic curve of the membrane electrode obtained in Example 4 of the present invention is shown in the figure. It can be seen that the voltages of the three groups of membrane electrodes obtained with different second electrodeposition times (2min, 5min or 10min) in Example 4 are 0.175V, 0.353V and 0.216V respectively; the maximum power density of the membrane electrode in Example 4 is 26mW / cm 2 、70.6mW / cm 2 、32.4mW / cm 2 It can be seen that in Example 4, when the Nafion content in the hydrophilic solution is 0.1% and the second electrodeposition time is 5 min, the performance of the membrane electrode is optimal.
[0084] Figure 7 The polarization characteristic curve of the membrane electrode obtained in Example 5 of the present invention is shown in the figure. It can be seen that the voltages of the three groups of membrane electrodes obtained with different second electrodeposition times (2min, 5min or 10min) in Example 5 are 0.232V, 0.368V and 0.453V respectively; the maximum power density of the membrane electrode in Example 5 is 55.2mW / cm 2 、80mW / cm 2 、203.85mW / cm 2 It can be seen that in Example 5, when the Nafion content in the hydrophilic solution is 1% and the second electrodeposition time is 10 min, the performance of the membrane electrode is optimal.
[0085] In summary, the present invention prepares an ordered membrane electrode through a two-step electrodeposition method: first, a hydrophilic layer containing an aminosilane coupling agent is formed on the surface of the microporous layer, and then a first electrodeposition is performed to deposit Pt nanoparticles on the surface of the hydrophilic layer to construct an ordered Pt nanoarray, wherein the aminosilane coupling agent has an anchoring and uniform distribution effect on the subsequently electrodeposited Pt nanoparticles, thereby increasing the effective contact area and stability of Pt; and then a second electrodeposition is performed to wrap a layer of perfluorosulfonic acid resin film on the surface of the Pt particles to effectively construct a three-phase interface and maximize the number of three-phase interfaces, thereby extending the effective reaction area to the entire cathode catalyst layer, thereby improving the membrane electrode reaction rate and the performance of the battery.
[0086] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing an ordered membrane electrode using a two-step electrodeposition method, characterized in that: The following steps are involved: S1, providing a gas diffusion layer, and forming a hydrophilic layer on the surface of the microporous layer of the gas diffusion layer; S2, first electrodeposition: immersing the product of step S1 in a platinum-containing electrodeposition solution to deposit metal Pt particles on the surface of the hydrophilic layer, and drying after the reaction is completed for later use; S3, second electrodeposition: immersing the product of step S2 in a perfluorosulfonic acid resin solution, depositing a perfluorosulfonic acid resin film on the surface of the metal Pt particles to form a cathode catalyst layer; S4, laminating the product of step S3 with a proton exchange membrane and an anode diffusion layer in sequence, and compounding them by hot pressing to obtain the ordered membrane electrode.
2. The method for preparing an ordered membrane electrode using a two-step electrodeposition method according to claim 1, characterized in that: The platinum-containing electrodeposition solution comprises chloroplatinic acid and perchloric acid.
3. The method for preparing an ordered membrane electrode using a two-step electrodeposition method as claimed in claim 2, characterized in that: In the platinum-containing electrodeposition solution, the mass fraction of the chloroplatinic acid is 0.5%-3%, and the mass fraction of the perchloric acid is 0.1%-4%.
4. The method for preparing an ordered membrane electrode using a two-step electrodeposition method according to claim 1, characterized in that: The mass fraction of the perfluorosulfonic acid resin solution is 0.1%-20%.
5. The method for preparing an ordered membrane electrode using a two-step electrodeposition method according to claim 1, characterized in that: In the step S2, a constant voltage is used to carry out the first electrodeposition reaction, the voltage is controlled at -0.1V to -1V, and the electrodeposition is carried out for 10min to 60min; In the step S3, a constant voltage is used to carry out the second electrodeposition reaction, the voltage is controlled at -0.1V to -0.4V, and the electrodeposition time is 2min to 20min.
6. The method for preparing an ordered membrane electrode using a two-step electrodeposition method according to claim 1, characterized in that: In step S1, the gas diffusion layer is immersed in a hydrophilic solution, and the hydrophilic layer is formed on the surface of the microporous layer of the gas diffusion layer through centrifugation and ultrasonic action.
7. The method for preparing an ordered membrane electrode using a two-step electrodeposition method as claimed in claim 6, characterized in that: The hydrophilic solution comprises: an aminosilane coupling agent, a perfluorosulfonic acid resin, an organic solvent and water, wherein the concentration of the aminosilane coupling agent is 90wt%-99wt%, and the concentration of the perfluorosulfonic acid resin is 0.01wt%-2wt%.
8. The method for preparing an ordered membrane electrode using a two-step electrodeposition method according to claim 1, characterized in that: In step S1, the gas diffusion layer is composed of a support layer and a microporous layer, the thickness of the support layer is 120 μm to 170 μm, and the total pore area is 50 m 2 / g-80m 2 / g, average pore size 60nm-80nm, porosity 25%-35%; the thickness of the microporous layer is 30μm-50μm, the total pore area is 50m 2 / g-100m 2 / g, average pore size 0.5nm-2nm, porosity 30%-50%.
9. An ordered membrane electrode prepared by the preparation method according to any one of claims 1 to 8.
10. A fuel cell, characterized in that: The fuel cell comprises the ordered membrane electrode as claimed in claim 9.